Seismic Evaluation of Retrofitting Technique Using Bracing Systems for Steel Multi-Story Building - Hassan Zainab Q; Al-Wazni Saad (BIO Web of Conferences, 2024)
A bracing system is the one of effective retrofitting methods for existing high buildings to support the lateral loads. Structural bracings increase the stiffness and stability of the building and the energy dissipation capacity. In this research, the numerical study of retrofitting a multi-story steel building near Imam Ali Holy Shrine in Najaf, Iraq has been conducted. The retrofitting mechanism includes a test of four different bracing systems such as X-bracing, V-bracing, Diagonal-bracing and IV-bracing located in the x and y-axis of the model. The seismic analysis using the elastic response spectrum method was performed for two types of earthquakes, weak and strong. The comparison among different parameters is discussed such as maximum lateral displacement, story drift ratio and base shear values. The seismic load was applied in two axes of the building model simultaneously and the results of the parameters in the x and y-axis were extracted. The results show that the retrofitting using four bracing system types increases the capacity of energy dissipation of the existing building model to seismic load by reducing the maximum lateral displacement in the x-axis by 55%, 44%, 41%, and 30% for X, IV, V and Diagonal-bracing, respectively. However, the X-bracing has a significant increase of the shear base value of the model by 39% and 49% in the x and y-axis, respectively, which means cost-effective compared with the other bracing types. Therefore, the IV-bracing type has an appropriate effect on the strength of the building against seismic load with reasonable cost-effectiveness.